2018
DOI: 10.1111/dmcn.13988
|View full text |Cite
|
Sign up to set email alerts
|

Muscle volume alterations after first botulinum neurotoxin A treatment in children with cerebral palsy: a 6‐month prospective cohort study

Abstract: Muscle atrophy after first botulinum neurotoxin A (BoNT-A) exposure in children with cerebral palsy is noted. Mild BoNT-A-induced muscle atrophy is still apparent 6 months after BoNT-A exposure. Hypertrophy is evident in soleus after gastrocnemius BoNT-A exposure. Total plantarflexor volume is unchanged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(78 citation statements)
references
References 27 publications
2
75
1
Order By: Relevance
“…The rational of this treatment combination is that paralysis, followed by passive immobilization in a neutral position, results in tissue elongation through physiological adaptation to prolonged stretch. However, few clinical studies reported the effects of BoNT-A treatment at the muscle level (10)(11)(12)(13)(14)(15)(16)(17)(18). Synthesis of existing clinical studies that include post-treatment assessment of muscle morphology is hindered by methodological differences between studies and lack of normalization to account for natural muscle growth.…”
Section: Introductionmentioning
confidence: 99%
“…The rational of this treatment combination is that paralysis, followed by passive immobilization in a neutral position, results in tissue elongation through physiological adaptation to prolonged stretch. However, few clinical studies reported the effects of BoNT-A treatment at the muscle level (10)(11)(12)(13)(14)(15)(16)(17)(18). Synthesis of existing clinical studies that include post-treatment assessment of muscle morphology is hindered by methodological differences between studies and lack of normalization to account for natural muscle growth.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of repeat dosing with BoNTA on muscle structure and function has not been studied in this paper but is recognised to be an important consideration in the long-term use of BoNTA. We have recently published on the impact on muscle volume and muscle structure following repeat dosing of BoNTA and presently we aim to minimise the dose of BoNTA used, rotate muscle selection where possible and ensure post intervention strength training, where appropriate [54][55][56]. It is now recognised that children with CP from socioeconomically disadvantaged settings are more likely to have reduced motor functional outcomes [57]; this study has not looked at any socio-economic determinants of health but this would be important in future research.…”
Section: Limitationsmentioning
confidence: 99%
“…There has been great enthusiasm in recent decades about the results of BoNT-A application in the treatment of lower limb spasticity in ambulatory children with SCP, but new studies have pointed out some adverse effects. A study by Caroline et al revealed that atrophy of the injected muscle after first application of BoNT-A in the gastrocnemius muscle in children with SCP is greater in comparison with further applications, and hypertrophy is evident in the soleus after exposure of the gastrocnemius to BoNT-A (6).…”
Section: Botulinum Toxin Type a For Spastic Cerebral Palsy: Is It Timmentioning
confidence: 99%